Dual-scale mullite nanofiber membrane and preparation method thereof
Through solution jet spinning technology and calcination treatment, a double-scale mullite nanofiber membrane was prepared, which solved the problems of high requirements for electrospinning equipment and limited fiber diameters, and achieved efficient filtration and low-cost nanofiber membrane production. for high temperature applications.
Patent Information
- Application Number
- CN202411376794.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, when preparing mullite nanofiber membranes, electrospinning technology equipment has high requirements and safety risks, and it is difficult to achieve mass production of nanofibers. The fiber diameter is limited, resulting in poor filtration performance, resulting in cost and energy consumption. Increase.
Using solution jet spinning technology, the spinning liquid is prepared by stirring components such as polyvinyl alcohol, hydroxypropyl methyl cellulose and silicon source, and the solution jet spinning treatment is carried out, and the double-scale mullite nanofiber is prepared in combination with calcination treatment. The membrane is designed with coarse and fine fiber staggered design to improve filtration efficiency and reduce costs and energy consumption.
A two-scale mullite nanofiber membrane that is stable at high temperatures has high filtration efficiency and low energy consumption. It also optimizes fiber diameters through interlaced design to improve pollutant interception performance and reduce production costs.
Smart Images

Figure CN119236696A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic fiber materials, and in particular to a dual-scale mullite nanofiber membrane and a preparation method thereof. Background Art
[0002] Ceramic fiber membrane is a kind of inorganic fiber membrane, which is often used as a high-performance filter material due to its unique structure and properties. Compared with organic fiber membrane, ceramic fiber membrane has good thermal stability, low volume density, strong chemical stability, flame retardant properties and excellent thermal insulation performance, making it have good application prospects in high-temperature filtration fields such as smelting, waste incineration, flue gas purification, etc.
[0003] Mullite is a mineral composed of aluminum silicate, and its chemical formula is generally expressed as 3Al2O3·2SiO2 or 2Al2O3·SiO2. It has the characteristics of fire resistance, high temperature stability, chemical stability, low thermal expansion coefficient, mechanical strength and electrical insulation, which makes it widely used in many fields such as refractory materials, aerospace, military industry and metallurgy.
[0004] Mullite fiber is a high temperature resistant ceramic fiber composed of a mullite phase. It has excellent high temperature creep resistance, corrosion resistance, light weight, softness, heat insulation and processability, making it an indispensable material in many high temperature applications.
[0005] Mullite fiber membrane can be prepared by matrix fiber impregnation method, which is simple and easy to promote, but the production cost is high and the quality of the obtained fiber is poor. Mullite fiber membrane can also be prepared by electrospinning technology.
[0006] Electrospinning is a common technology for producing fibers and fiber webs. The method is to apply high voltage to the spinning solution. During the electrospinning process, the solution is charged and overcomes its surface tension, forming a Taylor cone at the needle tip, and then stretching toward a ground plate or a rotating collector in the form of a jet. Electrospinning can produce continuous fiber components, such as fiber membranes, neatly arranged and patterned fiber webs, and random three-dimensional structures formed by multiple stacking of long fibers. The production efficiency of mullite nanofibers prepared by electrospinning technology is high, and fibers with diameters in the nanometer range (50-1000nm) can be prepared. They are high in purity, low in cost, and have strong continuity. They are also relatively easy to arrange, assemble, and process for application. However, electrospinning technology has high requirements for equipment and requires an external electric field, which poses certain experimental safety hazards. In addition, the yield of nanofibers prepared by electrospinning is low, making it difficult to achieve mass production of nanofibers, which greatly hinders the industrial production of nanofibers.
[0007] Solution jet spinning is a fiber production technology driven by compressed gas, which originates from the combination of electrospinning and traditional melt-blown technology. Compared with electrospinning, solution jet spinning technology does not require the action of a high-voltage electrostatic field, so it is safer and has lower equipment requirements. Regardless of the spinning technology used, the filtration performance of the mullite fiber membrane is greatly limited by the fiber diameter. With a large fiber diameter, the mullite fiber membrane has a poor interception effect on polluted particles and low filtration efficiency. With a small fiber diameter, the fiber membrane has a large resistance to gas, consumes more energy during use, and causes energy waste. Relevant researchers have solved this problem by increasing the thickness of the fiber membrane, which will cause a large increase in costs and also cause waste of resources. Summary of the invention
[0008] The purpose of the present invention is: Based on the above technical problem, the present invention provides a dual-scale mullite nanofiber membrane and a preparation method thereof.
[0009] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a dual-scale mullite nanofiber membrane, the method comprising the following steps:
[0010] (1) first stirring polyvinyl alcohol, hydroxypropyl methylcellulose, and deionized water to obtain a polymer template solution A;
[0011] Polyvinyl alcohol, hydroxypropyl methylcellulose and deionized water are separately added for a second stirring to obtain a polymer template solution B;
[0012] (2) stirring a silicon source, an aluminum source, and an acetic acid aqueous solution for a third time to obtain a precursor solution; the silicon source is tetraethyl orthosilicate, and the aluminum source is aluminum isopropoxide and aluminum nitrate nonahydrate in a mass ratio of 0.5:1 to 2:1;
[0013] (3) subjecting the precursor solution and the polymer template solution A to a fourth stirring to obtain a spinning solution A;
[0014] Stirring the precursor solution and the polymer template solution B for the fourth time to obtain a spinning solution B;
[0015] (4) Simultaneously injecting the spinning solution A and the spinning solution B into a solution jet spinning device for solution jet spinning treatment to obtain a precursor fiber membrane; the conditions of the solution jet spinning treatment meet the following conditions: air flow pressure of 10 to 25 kPa, spinning solution extrusion speed of 2 to 6 mL / h, spinning receiving distance of 55 to 75 cm, collection drum rotation speed of 400 rpm, reciprocating speed of 3.3 cm / s, ambient humidity ≤ 30%, and ambient temperature of 25°C;
[0016] (5) The precursor fiber membrane is calcined to obtain a dual-scale mullite nanofiber membrane.
[0017] Preferably, in step (1), the usage ratio of the polyvinyl alcohol to the hydroxypropyl methylcellulose is 1:1.
[0018] Further preferably, in step (1), the usage ratio of the polyvinyl alcohol to the deionized water is 1:10 or 1:6.
[0019] Preferably, in step (1), the conditions of the first stirring and the second stirring at least meet the following conditions: the temperature is 50 to 80° C., and the time is 2 to 5 hours.
[0020] Preferably, in step (2), the molar ratio of silicon element to aluminum element in the silicon source and the aluminum source is 1:3.
[0021] Preferably, in step (2), the pH value of the acetic acid aqueous solution is 2-4.
[0022] Preferably, in step (2), the amount of the acetic acid aqueous solution used is 6 mL relative to 0.9 g of tetrahexyl orthosilicate, or the amount of the acetic acid aqueous solution used is 12 mL relative to 1.8 g of tetrahexyl orthosilicate.
[0023] Preferably, in step (3), in the spinning solution A, the mass ratio of tetraethyl orthosilicate in the precursor solution to polyvinyl alcohol in the polymer template solution A is 3:2.
[0024] Further preferably, in step (3), in the spinning solution B, the mass ratio of tetraethyl orthosilicate in the precursor solution to polyvinyl alcohol in the polymer template solution B is 9:10.
[0025] Preferably, in step (4), the volume ratio of the spinning solution A to the spinning solution B is 1:1.
[0026] Further preferably, in step (4), the amount of the spinning solution A or the spinning solution B is 10 to 20 mL.
[0027] Preferably, in step (4), the conditions for the solution jet spinning treatment meet the following requirements: the air flow pressure is 20 kPa, the spinning solution extrusion rate is 3 mL / h, the spinning receiving distance is 60 cm, the rotation speed of the collecting drum is 400 rpm, the reciprocating speed is 3.3 cm / s, the ambient humidity is ≤30%, and the ambient temperature is 25°C.
[0028] Preferably, in step (5), the calcination treatment conditions at least meet the following requirements: heating to 1100° C. at a rate of 2 to 5° C. / min and maintaining the temperature at this temperature for 30 to 120 min.
[0029] The second aspect of the present invention provides a dual-scale mullite nanofiber membrane prepared by the method described in the first aspect of the present invention, wherein the dual-scale mullite nanofiber membrane contains mullite fiber I and mullite fiber II, and the average diameter of the mullite fiber I is 186nm, the average diameter of the mullite fiber II is 606nm, and the surface density of the dual-scale mullite nanofiber membrane is 3.8-7.1mg / cm 2 .
[0030] The dual-scale mullite nanofiber membrane and the preparation method thereof provided by the present invention have at least the following beneficial effects:
[0031] (1) The dual-scale mullite nanofiber membrane provided by the present invention is foldable and bendable, and can be used for a long time at a high temperature of 1200°C. The average diameters of the mullite fibers constituting the fiber membrane are 186nm and 606nm.
[0032] (2) The dual-scale mullite nanofiber membrane provided by the present invention has an average density of 3.8 mg / cm 2 When the airflow rate is 32L / min, the PM 0.3 The filtration efficiency is 98.23% and the pressure drop is 141Pa.
[0033] (3) When the polymer is used as a template, if the content is low, the viscosity of the spinning solution is low, and the spinnability of the spinning solution is poor; if the content is high, the viscosity of the spinning solution is high, and the fiber diameter is large, then the filtration efficiency of the fiber membrane is limited. For the polymer template, the present invention uses hydroxypropyl methylcellulose derivatives to replace part of the traditional polymer to adjust the fiber diameter. When the viscosity of the spinning solution is reduced, the spinnability of the spinning solution is not affected, and mullite fibers with a wider diameter range can be prepared by solution jet spinning, which is convenient for adjusting the fiber diameter according to the application scenario.
[0034] (4) To improve the filtration performance of fiber membranes, traditional methods increase filtration efficiency while increasing energy or cost. The present invention adopts the design concept of staggered coarse and fine fiber matching to improve filtration efficiency while reducing energy consumption and production costs. Among them, fine fibers play a role in intercepting pollutant particles, and coarse fibers inhibit the densification of fiber membranes, reducing the resistance generated during the filtration process. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a SEM scanning electron microscope image of the dual-scale mullite nanofiber membrane obtained in Example 1 of the present invention;
[0036] Figure 2 is a SEM scanning electron microscope image of fine fibers in the dual-scale mullite nanofiber membrane obtained in Example 1 of the present invention;
[0037] Figure 3This is a SEM scanning electron microscope image of the coarse fibers in the dual-scale mullite nanofiber membrane obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0039] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.
[0040] Example 1
[0041] This example is used to provide a method for preparing a dual-scale mullite nanofiber membrane, the method comprising the following steps:
[0042] (1) adding 0.6 g of polyvinyl alcohol and 0.6 g of hydroxypropyl methylcellulose to 6 mL of deionized water, heating to 80° C., and mechanically stirring at the same temperature for 5 h to obtain a polymer template solution A;
[0043] 1 g of polyvinyl alcohol and 1 g of hydroxypropyl methylcellulose were added to 6 mL of deionized water, heated to 80° C., and mechanically stirred at the same temperature for 5 h to obtain a polymer template solution B.
[0044] (2) 0.9 g of tetraethyl orthosilicate, 1.6 g of aluminum nitrate nonahydrate, and 1.8 g of aluminum isopropoxide were slowly added to 6 mL of an acetic acid aqueous solution having a pH of 3, and mechanically stirred at room temperature until they were completely dissolved to obtain a precursor solution.
[0045] (3) adding 6.5 mL of the precursor solution to the polymer template solution A, and mechanically stirring the mixture at room temperature to obtain a spinning solution A;
[0046] 6.5 mL of the precursor solution was added to the polymer template solution B, and the mixture was mechanically stirred at room temperature to obtain a spinning solution B.
[0047] (4) simultaneously injecting 10 mL of the spinning solution A and 10 mL of the spinning solution B into a solution jet spinning device for solution jet spinning to obtain a precursor fiber membrane;
[0048] The conditions for the solution jet spinning treatment are as follows: air flow pressure of 20 kPa, spinning solution extrusion speed of 3 mL / h, spinning receiving distance of 60 cm, collection drum rotation speed of 400 rpm, reciprocating speed of 3.3 cm / s, ambient humidity ≤30%, and ambient temperature of 25°C.
[0049] (5) The precursor fiber membrane was placed in a muffle furnace for calcination to obtain a surface density of 3.8 mg / cm 2 Dual-scale mullite nanofiber membrane;
[0050] The calcination treatment conditions are as follows: heating to 1100° C. at a rate of 5° C. / min and maintaining the temperature at this temperature for 120 min.
[0051] Example 2
[0052] This example is used to provide a method for preparing a dual-scale mullite nanofiber membrane, the method comprising the following steps:
[0053] (1) adding 1.2 g of polyvinyl alcohol and 1.2 g of hydroxypropyl methylcellulose to 12 mL of deionized water, heating to 70° C., and mechanically stirring at the same temperature for 5 h to obtain a polymer template solution A;
[0054] 2 g of polyvinyl alcohol and 2 g of hydroxypropyl methylcellulose were added to 12 mL of deionized water, heated to 70° C., and mechanically stirred at the same temperature for 5 h to obtain a polymer template solution B.
[0055] (2) 1.8 g of tetraethyl orthosilicate, 3.2 g of aluminum nitrate nonahydrate, and 3.6 g of aluminum isopropoxide were slowly added to 12 mL of an acetic acid aqueous solution having a pH of 3, and mechanically stirred at room temperature until they were completely dissolved to obtain a precursor solution.
[0056] (3) adding 13 mL of the precursor solution to the polymer template solution A, and mechanically stirring the mixture at room temperature to obtain a spinning solution A;
[0057] 13 mL of the precursor solution was added to the polymer template solution B, and the mixture was mechanically stirred at room temperature to obtain a spinning solution B.
[0058] (4) simultaneously injecting 20 mL of the spinning solution A and 20 mL of the spinning solution B into a solution jet spinning device for solution jet spinning to obtain a precursor fiber membrane;
[0059] The conditions for the solution jet spinning treatment are as follows: air flow pressure of 20 kPa, spinning solution extrusion speed of 3 mL / h, spinning receiving distance of 60 cm, collection drum rotation speed of 400 rpm, reciprocating speed of 3.3 cm / s, ambient humidity ≤30%, and ambient temperature of 25°C.
[0060] (5) The precursor fiber membrane was placed in a muffle furnace for calcination to obtain a surface density of 7.1 mg / cm 2 Dual-scale mullite nanofiber membrane;
[0061] The calcination treatment conditions are as follows: heating to 1100° C. at a rate of 5° C. / min and maintaining the temperature at this temperature for 120 min.
[0062] Comparative Example 1
[0063] The method of Example 1 is followed, except that in step (1), the same amount of carboxymethyl cellulose is used instead of the hydroxypropyl methyl cellulose, and the remaining steps and parameters are the same as in Example 1.
[0064] The inventors of the present invention have found that when carboxymethyl cellulose is used instead of hydroxypropyl methyl cellulose, the prepared spinning solution cannot be used to prepare fibers using the solution jet spinning technology.
[0065] Comparative Example 2
[0066] The method of Example 1 is followed, except that in step (2), the aluminum source is aluminum isopropoxide and aluminum nitrate nonahydrate in a mass ratio of 1:4, and the remaining steps and parameters are the same as in Example 1.
[0067] The inventors of the present invention have found that in step (2), when the content of aluminum nitrate nonahydrate in the aluminum source is increased, the prepared spinning solution cannot be used to prepare fibers using the solution jet spinning technology.
[0068] Comparative Example 3
[0069] The method of Example 1 is followed, except that in step (3), in the spinning solution A, the mass ratio of tetraethyl orthosilicate in the precursor solution to polyvinyl alcohol in the polymer template solution A is 1:3, and the remaining steps and parameters are the same as in Example 1.
[0070] The inventors of the present invention found that in step (3), the proportion of the polymer solution in the spinning solution relative to the precursor solution was too high, and the viscosity of the prepared spinning solution was too high, making it impossible to prepare fibers using the solution jet spinning technology.
[0071] Comparative Example 4
[0072] The method of Example 1 was followed, except that in step (4), the volume of spinning solution A and spinning solution B was 5 mL, and the remaining steps and parameters were the same as in Example 1.
[0073] The inventors of the present invention found that in step (4), the average surface density of the dual-scale mullite fiber membrane prepared was too small, the filtration efficiency was not high, and it could not meet the application requirements.
[0074] Comparative Example 5
[0075] The method of Example 1 was followed, except that in step (4), the volume of spinning solution A and spinning solution B was 30 mL, and the remaining steps and parameters were the same as in Example 1.
[0076] The inventors of the present invention have found that in step (2), the average surface density of the dual-scale fiber membrane prepared is too large, and the filtration efficiency does not increase significantly with the increase of the surface density, but the pressure drop increases significantly with the increase of the surface density, and the filtration performance of the fiber membrane decreases. In addition, the consumption of raw materials increases, resulting in an increase in costs.
[0077] Test Example 1
[0078] The dual-scale mullite nanofiber membranes obtained in the above examples and comparative examples were subjected to SEM scanning electron microscope tests.
[0079] For example, Figure 1 This is a SEM scanning electron microscope image of the dual-scale mullite nanofiber membrane obtained in Example 1 of the present invention. Figure 1 It can be seen that coarse fibers and fine fibers are staggered and evenly distributed, the gaps between the fibers are moderate, the fine fibers can intercept pollutant particles, and the coarse fibers can inhibit the densification of the fiber membrane and reduce the resistance generated during the filtration process.
[0080] Figure 2 The SEM scanning electron microscope image of the fine fibers in the dual-scale mullite nanofiber membrane obtained in Example 1 of the present invention is composed of Figure 2 It can be seen that the pores between fibers in the mullite fiber membrane composed of fine fibers are small, and the pollutant interception effect is good, but the air resistance generated during filtration is large.
[0081] Figure 3 The SEM scanning electron microscope image of the coarse fibers in the dual-scale mullite nanofiber membrane obtained in Example 1 of the present invention is composed of Figure 3 It can be seen that the pores between fibers in the mullite fiber membrane composed of coarse fibers are larger, and the air resistance generated during filtration is small, but the interception of pollutants is limited.
[0082] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a dual-scale mullite nanofiber membrane, characterized in that: The method comprises the following steps: (1) first stirring polyvinyl alcohol, hydroxypropyl methylcellulose, and deionized water to obtain a polymer template solution A; Polyvinyl alcohol, hydroxypropyl methylcellulose and deionized water are separately added for a second stirring to obtain a polymer template solution B; (2) stirring a silicon source, an aluminum source, and an acetic acid aqueous solution for a third time to obtain a precursor solution; the silicon source is tetraethyl orthosilicate, and the aluminum source is aluminum isopropoxide and aluminum nitrate nonahydrate in a mass ratio of 0.5:1 to 2:1; (3) subjecting the precursor solution and the polymer template solution A to a fourth stirring to obtain a spinning solution A; Stirring the precursor solution and the polymer template solution B for the fourth time to obtain a spinning solution B; (4) Simultaneously injecting the spinning solution A and the spinning solution B into a solution jet spinning device for solution jet spinning treatment to obtain a precursor fiber membrane; the conditions of the solution jet spinning treatment meet the following conditions: air flow pressure of 10 to 25 kPa, spinning solution extrusion speed of 2 to 6 mL / h, spinning receiving distance of 55 to 75 cm, collection drum rotation speed of 400 rpm, reciprocating speed of 3.3 cm / s, ambient humidity ≤ 30%, and ambient temperature of 25°C; (5) The precursor fiber membrane is calcined to obtain a dual-scale mullite nanofiber membrane.
2. The method according to claim 1, wherein: In step (1), the ratio of the polyvinyl alcohol to the hydroxypropyl methylcellulose is 1:1; And / or, in step (1), the usage ratio of the polyvinyl alcohol to the deionized water is 1:10 or 1:6; and / or, In step (1), the conditions of the first stirring and the second stirring at least meet the following requirements: the temperature is 50 to 80° C. and the time is 2 to 5 hours.
3. The method according to claim 1 or 2, wherein: In step (2), the molar ratio of silicon element to aluminum element in the silicon source and the aluminum source is 1:
3.
4. The method according to claim 1 or 2, wherein: In step (2), the pH value of the acetic acid aqueous solution is 2 to 4; And / or, in step (2), the amount of the acetic acid aqueous solution used is 6 mL relative to 0.9 g of tetrahexyl orthosilicate, or the amount of the acetic acid aqueous solution used is 12 mL relative to 1.8 g of tetrahexyl orthosilicate.
5. The method according to claim 1 or 2, wherein: In step (3), in the spinning solution A, the mass ratio of tetraethyl orthosilicate in the precursor solution to polyvinyl alcohol in the polymer template solution A is 3:
2.
6. The method according to claim 1 or 2, wherein: In step (3), in the spinning solution B, the mass ratio of tetraethyl orthosilicate in the precursor solution to polyvinyl alcohol in the polymer template solution B is 9:
10.
7. The method according to claim 1 or 2, wherein: In step (4), the volume ratio of the spinning solution A to the spinning solution B is 1:1; And / or, in step (4), the amount of the spinning solution A or the spinning solution B is 10 to 20 mL.
8. The method according to claim 1 or 2, wherein: In step (4), the conditions for the solution jet spinning treatment are as follows: the air flow pressure is 20 kPa, the spinning solution extrusion rate is 3 mL / h, the spinning receiving distance is 60 cm, the rotation speed of the collecting drum is 400 rpm, the reciprocating speed is 3.3 cm / s, the ambient humidity is ≤30%, and the ambient temperature is 25°C.
9. The method according to claim 1 or 2, wherein: In step (5), the calcination treatment conditions at least meet the following requirements: heating to 1100° C. at a rate of 2 to 5° C. / min and maintaining the temperature at this temperature for 30 to 120 min.
10. A dual-scale mullite nanofiber membrane prepared by the method according to any one of claims 1 to 9, characterized in that: The dual-scale mullite nanofiber membrane contains mullite fiber I and mullite fiber II, and the average diameter of the mullite fiber I is 186nm, the average diameter of the mullite fiber II is 606nm, and the surface density of the dual-scale mullite nanofiber membrane is 3.8-7.1mg / cm 2 .
